Fabrication and characterization of planar dipole antenna and schottky diode for on-chip electronic device integration - Mustafa, Farahiyah (2010)
Recent revolutionary progress of the internet and wireless technologies has created a concept of the "ubiquitous network society" for this 21st century. A so-called Intelligent Quantum (IQ) chip has been proposed as the promising electronic device for the ubiquitous network society environments. An IQ chip is an III-V semiconductor chip with sizes of millimeter square or less where nanometer scale quantum processors and memories are integrated on the same chip with other capabilities of wireless power supply and various sensing functions. It is an attempt to endow "more intelligence" than simple identification (ID) like in radio frequency identification detector (RFID) chips to semiconductor chips so that they can be utilized as versatile tiny "knowledge vehicles" to be embedded anywhere in the society, or even within the bodies of human beings and other living species. This study is carried out to focus on the development of wireless microwave power transmission/supply and detector technology. Integrated on-chip device (integration between antenna and Schottky diode) is one of the most potential devices to be integrated on the IQ chip to act as the wireless power supply as well as power detector. The feasibility of direct integration between planar dipole antennas with Schottky diode via coplanar waveguide (CPW) transmission line without any matching circuits inserted between them for nanosystem application is studied. First, the fabrication and radio frequency (RF) characterization of planar dipole antenna facilitated with CPW structure on semi-insulated gallium arsenide (GaAs) are performed. The return loss of dipole antennas are evaluated by varying their lengths, widths and also metal thicknesses for the purpose of use in the super high frequency (SHF) band. Experimentally, the return loss down to -54 dB with a metal thickness of 50 nm is obtained. The difference is only 2 % - 4 % between simulated and measured results for the frequency bandwidth at -10 dB. It is shown that the fundamental resonant frequency of dipole antennas can be controlled by the dipole length but unchanged with the width and metal thickness. Next, the fabrication, direct current (DC) and RF characterization of the AlGaAs/GaAs high-electron mobility-transistor (HEMT) Schottky diode is performed. The fabricated devices show good rectification with a Schottky barrier height of 0.5289 - 0.5468 eV for Nickel/Gold (Ni/Au) metallization. The differences of Schottky barrier height from theoretical value are due to the fabrication process and smaller contact area. The RF signals are well detected and rectified by the fabricated Schottky diodes and stable DC output voltage is obtained. The cut-off frequency up to 20 GHz is estimated in direct injection experiments. The output current is in the range of several tens of microamperes (µA) which is adequate for low current device application. Finally, an integrated device is fabricated and tested in direct RF irradiation. However, a reception of RF signal by dipole antenna is weak. Further considerations on the polarization of irradiation and radiation distance of the antenna need to be carried out. These results provide new breakthrough ideas for the direct on-chip integration technology towards realization of fast RF damaging signal detection and towards realization of ultra-low power on-chip rectenna technology for nanosystem application.